THE EFFECT OF WORK DISCIPLINE AND WORK MOTIVATION TOWARDS THE PERFORMANCES OF LPP RRI EMPLOYEES - Isnaini; Hamsani; Andriyansah (Universitas Lambung Mangkurat, 2020)
This research in conducted to find the relationship between work discipline and work motivation towards the performances both partially and simultaneously of LPP RRI employees. This research employs a descriptive quantitative method to know the effect of independent variable (X) and the dependent variable (Y), with the respondents of LPP RRI employees of Belajasumba regions (RRI Bengkulu, RRI Bandar Lampung, RRI Jambi, RRI South Sumatra, and RRI Bangka Belitung), with the total number of 125 respondents, using the instrument of research such as questionnaires spread by online link. To test and analyze the data, the writer employs software program of SPSS version 23. The result of the study shows that the work discipline factor has a positive effect with the regression coefficient score of 0.264 by the statistical t score of 3.304 with the significance level of 0.001 < 0.05 meaning that the hypothesis 0 of this research is accepted. The work motivation factor also has a positive effect with the t count score of 7.762 with the significance level of 0.000 < 0.05 meaning that the hypothesis 0 of this research is accepted. The result of f test analysis shows that f count score of 139.267 with the significant level of 0.05 in which the significance score of 0.001 < 0.05 meaning that the hypothesis is accepted. Then, the result of determination coefficient (R2) gets the result score of 0.695. This means that 69.5% of employees’ performance variable of variation (Y) can be determined by the work discipline (X1) dan work motivation (X2), whereas the rest 30.5% portion is determined by other factors of variables that are not tested in this research.